Teologi Ambivalensi Monarki Awal: Dialektika Otoritas Ilahi dan Inisiatif Manusia dalam 1 Samuel 8-12 - Silalahi, Binsar Pandapotan; Kurniawan, Kezia Sharon (Sekolah Tinggi Teologi Berea, Salatiga, 2025)
This article analyzes the ambivalence of monarchy in 1 Samuel 8-12 by emphasizing the dynamic relationship between YHWH and Saul as the first king of Israel. This narrative presents the monarchy as an institution born of tension: on the one hand, it was requested by the people as a rejection of divine rule, but on the other hand, it was facilitated through Saul's anointing by the prophet Samuel. Previous studies have focused more on historical, literary, or ethical dimensions, thus not paying particular attention to the theological-ambivalent aspects of the early monarchy. The novelty of this research lies in placing 1 Samuel 8-12 as the main locus for examining the dialectic between divine authority and human initiative. This study uses the method of narrative exegesis of the Masoretic text to examine the literary structure, repetition of key diction, and patterns of relationships in the narrative. The results of the analysis show that the early monarchy is narratively positioned as an ambivalent institution, which is both legitimized and criticized, thus forming a theological strategy that affirms the limitations of human power within the framework of its relationship with divine authority.